Outbreak of acute coccidiosis in housed West African Dwarf goats - Nwosu, C.O. (1996)
In February 1991,16 West African Dwarf/Djallonke goat kids aged 3-4 months were purchased from two rural communities from south western Nigeria and divided evenly into 4 experimental groups (I-IV) and housed in fly-proof pens with concrete floors and bedding of litter changed weekly. Faecal egg and oocyst counts and packed cell voloume (PCV) were determined at the time of purchase and repeated 32 days later. Faecal egg and oocyt counts were low at the time of purchase. At day 32, nematode eggs were low or absent in faeces but significantly high (p